Coherence Analysis of Symmetric Star Topology Networks - Gao, Haiping; Zhu, Jian; Chen, Xing; Zhang, Long; Li, Xianyong (Frontiers in Physics, 2022)
In the background of noise interference, the study of network coherence is beneficial to improve the anti-interference ability of the network, so as to improve the stability of the network. In this paper, the first-order coherence of three kinds of symmetric star topology networks are studied by using the theory of network science. Firstly, three kinds of symmetric star topology network models are given. Secondly, the first-order coherence indexes of these network models are calculated by using matrix theory. The relationships among the first-order coherence of the network and branch length and the number of branches change are obtained by numerical simulation. Finally, we found that the third network has the best first-order coherence, and the change of branch length has more effective impact on network coherence.